Barriers to smoking cessation: a qualitative study from the perspective of primary care in Malaysia - Siew-Ting Ooi; Kooi-Yau Chean; Lee Gan Goh; Kah-Weng Liew; Chia-Chia Tan; Xin-Ling Choi; Kean-Chye Tan (BMJ Open)
Objectives This qualitative study aims to construct a model of the barriers to smoking cessation in the primary care setting.Design Individual in-depth, semistructured interviews were audio-taped, then verbatim transcribed and translated when necessary. The data were first independently coded and then collectively discussed for emergent themes using the Straussian grounded theory method.Participants and setting Fifty-seven current smokers were recruited from a previous smoking related study carried out in a primary care setting in Malaysia. Current smokers with at least one failed quit attempts were included.Results A five-theme model emerged from this grounded theory method. (1) Personal and lifestyle factors: participants were unable to resist the temptation to smoke; (2) Nicotine addiction: withdrawal symptoms could not be overcome; (3) Social cultural norms: participants identified accepting cigarettes from friends as a token of friendship to be problematic; (4) Misconception: perception among smokers that ability to quit was solely based on one’s ability to achieve mind control, and perception that stopping smoking will harm the body and (5) Failed assisted smoking cessation: smoking cessation services were not felt to be user-friendly and were poorly understood. The themes were organised into five concentric circles based on time frame: those actionable in the short term (themes 1 and 2) and the long term (themes 3, 4, 5).Conclusions Five themes of specific beliefs and practices prevented smokers from quitting. Clinicians need to work on these barriers, which can be guided by the recommended time frames to help patients to succeed in smoking cessation.